2021
DOI: 10.1111/ocr.12483
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial and airway morphology of individuals with oculoauriculovertebral spectrum

Abstract: Objectives The objectives of this study were to characterize the craniofacial and airway morphology of oculo‐auriculo‐vertebral spectrum (OAVS) individuals using computed tomography (CT) examination. Setting and Sample Population This sample included individuals in the age range from 5 to 14 years, consisted of a group of 18 OAVS individuals (12 females and 6 males), Pruzansky‐Kaban1 IIB and III and by a paired control group matched by age and sex for comparison of morphometric and airway variables. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…4 Multiple other studies have demonstrated results similar to the present study. [17][18][19] . Therefore, the general assumption that GS affects men more frequently as compared with women should be re-examined using a multicenter study or an up-to-date systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…4 Multiple other studies have demonstrated results similar to the present study. [17][18][19] . Therefore, the general assumption that GS affects men more frequently as compared with women should be re-examined using a multicenter study or an up-to-date systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with craniocervical instability had extracraniofacial anomalies (OMENS Plus), the main changes being radial; of those who did not present instability, 68.5% had extracraniofacial alterations, which also suggests that patients with more extracraniofacial findings tend to have higher craniocervical instability. In these patients, the airway may also be affected 14…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, the airway may also be affected. 14 Due to the rarity of the condition evaluated in these patients, as well as the judicious choice of individuals for the evaluation of this study, a descriptive analysis was chosen so that the observed findings can serve as a basis for professionals who monitor patients with OAVS. Because it is a cross-sectional retrospective study, the study was subject to limitations in its methodology, such as the collection bias inherent in data involving handwritten records and the bias in selecting a referral center for the treatment of cleft lip and palate, as a higher prevalence of cleft lip and palate than found in other studies was observed.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus about the nomenclature and minimal criteria for diagnosis in CFM. Several terms have been used to represent the combination of clinical findings, such as first and second branchial arches syndrome, oculoauriculovertebral dysplasia, hemifacial microsomia, Goldenhar syndrome, oculoauriculovertebral spectrum and, most recently, craniofacial microsomia 2–8…”
mentioning
confidence: 99%
“…Several terms have been used to represent the combination of clinical findings, such as first and second branchial arches syndrome, oculoauriculovertebral dysplasia, hemifacial microsomia, Goldenhar syndrome, oculoauriculovertebral spectrum and, most recently, craniofacial microsomia. [2][3][4][5][6][7][8] This condition presents etiologic and pathogenic heterogeneity. Environmental factors, such as maternal diabetes, chromosomal anomalies and genetic involvement with autosomal dominant inheritance or autosomal recessive inheritance patterns, complex inheritance-genetic factors associated with environmental factors-and maternal exposition to teratogenic drugs have been described in the medical literature.…”
mentioning
confidence: 99%